The checklist manifesto how to get things right - Gawande, Atul (Picador, 2009)
The modern world has given us stupendous know-how. Yet avoidable failures continue to plague us in health care, government, the law, the financial industry—in almost every realm of organized activity. And the reason is simple: the volume and complexity of knowledge today has exceeded our ability as individuals to properly deliver it to people—consistently, correctly, safely. We train longer, specialize more, use ever-advancing technologies, and still we fail.